Adoption of a protocol among healthcare workers to improve the containment of the coronavirus disease 2019 outbreak - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2022)
The coronavirus disease-2019 (COVID-19) outbreak, which was first detected in the Wuhan city of China has been considered eligible to meet the requirements of the Public Health Emergency of International Concern. It is a fact that healthcare workers constitute the first line of defense against the infection and are involved in patient care related activities by compromising their own safety and quality of life. The current available disease trends neither indicate about the extent of the infection in hospital settings nor about the potential risk factors among health workers. In an attempt to bridge this gap, a protocol has been formulated to assess the extent of the infection and the risk factors which can facilitate the acquisition of the infection. Further, based on the proposed protocol, we can get vital insights about transmissibility and routes of transmission by periodically analyzing laboratory specimens as a part of follow-up. In conclusion, health workers are at the forefront in containing the COVID-19 outbreak amidst all uncertainty and thus it is our responsibility to adopt a standard protocol not only to safeguard them, but also simultaneously generate adequate evidence for better prevention and control of the disease.